Analysis of an Alcohol Use Prevention Program for Undergraduate Students - Hunnicutt Hollenbaugh, K. Michelle (Journal of addictions & offender counseling, 2019)
The authors analyzed data from an online alcohol abuse prevention test. Results showed no statistically significant difference between students charged with university alcohol-related offenses and those who had not been charged. Implications for counselors and suggestions for future research are discussed.